The Project-Based Learning Model Improves Science Knowledge Competencies of Class V Elementary School Students - Ni Made Prema Wahini; Ni Nyoman Ganing (MIMBAR PGSD Undiksha, 2023)
The weak learning process is different from the objectives of science lessons. The teacher only conveys concepts to students that must be memorized without using learning media. This study aims to analyze the effect of the Project Based Learning model on the science knowledge competence of fifth-grade students in elementary school. This type of research is quasi-experimental with a non-equivalent control group design. The population of this study amounted to 190 students of fifth-grade elementary school. The sample in the experimental group was 31 people, and the control group was 36 fifth-grade elementary school students. The data collection method used is the objective test method. Research data were analyzed using descriptive and inferential statistical techniques (t-test). The results of data analysis obtained the average pre-test score of the experimental group 14 in the low category, and the average pre-test in the control group was 12.41 in the low category. The average post-test of the experimental group was 18.80 in the medium category, while the average post-test in the control group was 15.33 in the low category. Based on the results of the t-test analysis, it was found that the Project Based Learning model significantly influenced the science knowledge competence of fifth-grade elementary school students. It was concluded that the Project Based Learning model could improve the science knowledge of fifth-grade elementary school students.